Bronchopulmonary foregut malformation with severe hemoptysis in advanced age: a case report and literature review - Cai, Cheng-Sen; Li, Bin; Yuan, Yu-chun; Fu, Li-na; Zhang, Xiao-ye; Wang, Jun (Frontiers in Medicine, 2024)
Bronchopulmonary foregut malformation (BPFM) is a rare developmental malformation disease due to embryonic defects, with an even rarer occurrence in adults. We report a diagnosed case in an adult patient, and notably, this is the first reported case of such advanced age. Additionally, she experienced coughing up approximately 1 liter of blood and partial lung tissue, accompanied by respiratory failure and shock. Following treatment with transcatheter arterial embolization, her condition improved, and she has remained stable during follow-up. We present a case report and conducted a systematic review on this particular case.